Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fmech.2019.00033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MHD Lubrication and Textured Surface in EHL Line Contact

Abstract: The present numerical study investigates the combined effect of micro-texture and magneto hydrodynamic lubrication behavior on the performance of elastohydrodynamic lubrication (EHL) line contact. Micro-textures, which are found in the inlet zone of a contacting surface, are studied, and modified Reynolds, elasticity, and load balance equations have been solved using Finite element analysis (FEA) and Generalized Minimal Residual Method (GMRES). A parametric study has been performed to optimize the micro-textur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The magnetic force exerted on the fluid may involve velocity. Instead of generalized pressure, a new function representing the effect of the magnetic force could be derived and added in the modified Reynolds equation (Hughes and Elco, 1962;Lin et al, 2009;Jadhav et al, 2019).…”
Section: Ferrofluids In Lubricationmentioning
confidence: 99%
“…The magnetic force exerted on the fluid may involve velocity. Instead of generalized pressure, a new function representing the effect of the magnetic force could be derived and added in the modified Reynolds equation (Hughes and Elco, 1962;Lin et al, 2009;Jadhav et al, 2019).…”
Section: Ferrofluids In Lubricationmentioning
confidence: 99%
“…Marian et al (Marian et al, 2019) discussed the effects of structural parameters such as the depth and diameter of micro-textures and the relative position of microtexture and counter-body on lubrication and friction on point contact. Jadhav et al (Jadhav et al, 2019) investigated the effects of spherical, rectangular and triangular textures on the lubrication characteristics of line contact EHL based on a magnetohydrodynamic lubrication model. There are many studies on the lubrication characteristics of micro-textured surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Gelinck and Schipper 18 found that the lubrication state of the spur gear changed from EHL to mixed lubrication (ML) when the velocity and the roughness of the gear surfaces are changed. With more conditions taken into consideration, Jadhav et al 19 investigated the combined effects of micro-texture and magnetohydrodynamic lubrication behavior on the performance of an EHL line contact. Ebner et al 20 investigated the effect of starved lubrication on the operating behavior of EHL contacts.…”
Section: Introductionmentioning
confidence: 99%